A numerical study of open atmospheric balloon dynamics - Alexander, P. (2003)
The dynamics of open balloons in an atmosphere may be studied with a body-fluid coupled model. A numerical approach is required to solve the corresponding equation set. Solutions under different conditions are obtained here for the vertical and one horizontal direction. Relevant dynamical features during ascent, flotation, and descent depend on balloon thermodynamics, wind, air small-scale turbulence, and perturbations to the background atmosphere. After analysis of the results it is found that approximate analytical solutions may be found in certain cases. The effect of nonlinear drag on balloon oscillation period and damping near flotation is evaluated. © 2003 American Institute of Physics.